Long-term low salt diet increases blood pressure by activation of the renin-angiotensin and sympathetic nervous systems - Wang, Jialiang (Clin Exp Hypertens, 2018)
BACKGROUND: The aim of this study was to investigate the effect of long-term low salt diet on blood pressure and its underlying mechanisms. METHODS: Male Sprague-Dawley (SD) rats were divided into normal salt diet group (0.4%) and low salt diet group (0.04%). Blood pressure was measured with the non-invasive tail-cuff method. The contractile response of isolated mesenteric arteries was measured using a small vessel myograph. The effects on renal function of the intrarenal arterial infusion of candesartan (10 µg/kg/min), an angiotensin II receptor type 1 (AT(1)R) antagonist, were also measured. The expressions of renal AT(1)R and mesenteric arterial α(1A), α(1B), and α(1D) adrenergic receptors were quantified by immunoblotting. Plasma levels of angiotensin II were also measured. RESULTS: Systolic blood pressure was significantly increased after 8 weeks of low salt diet. There were no obvious differences in the renal structure between the low and normal salt diet groups. However, the plasma angiotensin II levels and renal AT(1)R expression were higher in low than normal salt diet group. The intrarenal arterial infusion of candesartan increased urine flow and sodium excretion to a greater extent in the low than normal salt diet group. The expressions of α(1A) and α(1D), but not α(1B), adrenergic receptors, and phenylephrine-induced contraction were increased in mesenteric arteries from the low salt, relative to the normal salt diet group. CONCLUSION: Activation of the renin-angiotensin and sympathetic nervous systems may be involved in the pathogenesis of long-term low salt diet-induced hypertension.